Imaginarios y Prácticas Comunicativas en el Ecuavóley. - Beltrán Navarro, Edgar Andrés (2015)
This academic article is the product of an investigation process based on a systematic, analytical and criticism method to research about the concept of collective imagination applied to the practice of ecuavolley, a sport that contains singular features from ecuadorian culture. This sporting activity constructed a combination of ideas and symbols that have changed in the collective awareness in keeping with time. In order to corroborate this fact development through the time, this investigation shows the communicative practices into this sport. The matter that tackles this article is if ¿the communicative practices of ecuavolley represent the collective imagination of ecuadorians? This document shows the development of a research process which will use investigation supports as interviews and field observations. In order to corroborate this development, this investigation showed those communicative practices into this sport. The theoretical support proposes to Edgar Morín and his theory of imagination collective, he sets that the collective imagination is the social collective mind, and in a general mode, it proposes to Castoriadis, Piche, Alejandro Peñuela, Paul Ricoeur and other authors more to realize this study that leaves from this proposal that establishes a dynamic between imagination and society, also from a broad bibliographic revision of concepts and theories related within the idea of imagination and communicative practices with volley as a popular sport in Ecuador.